Nucleation and Crystal Growth in Laser-Patterned Lines in Glasses - Komatsu, Takayuki; Honma, Tsuyoshi (Frontiers in Materials, 2016)
Laser-induced crystallization is a new method for the design and control of the crystallization of glasses and opens a new door in the study of nucleation and crystal growth in glasses. Nonlinear optical Sm-doped -BaB2O4 (-BBO) crystal lines were patterned by continuous wave Yb:YVO4 fiber laser (wavelength 1080 nm) in 8Sm2O3-42BaO-50B2O3 glass as an example, and nucleation and crystal growth behaviors in the laser-patterned bending and crossing lines were examined. It was confirmed that the growth of c-axis oriented -BBO crystals follows along the laser scanning direction even if laser scanning direction changes. The model of self-organized homo-epitaxial crystal growth was demonstrated for the orientation of -BBO crystals at the crossing point of two lines, in which the first crystal line at the crossing point acts as nucleation site for the second crystal line. This study proposes a new crystal growth technology.